Factors affecting the grieving process after perinatal loss - Makiko Kishimoto; Arisa Yamaguchi; Marina Niimura; Miki Mizumoto; Tatsuo Hikitsuchi; Kohei Ogawa; Nobuaki Ozawa; Yoshiyuki Tachibana (BMC, 2021)
Abstract Background Factors associated with the grief process in response to perinatal loss have been investigated. However, few studies focused on the intrapersonal factors, such as developmental and personality traits. Hence, this study aimed to investigate medical and psychosocial risk factors, including inter- and intrapersonal factors for the development of complicated grief following perinatal loss, while considering emotional support. Methods A total of 50 patients who were treated for grief due to perinatal loss at the National Center for Child Health and Development were divided into two groups according to the treatment period (< 6 months: n = 28; ≥ 6 months: n = 22). We compared medical and psychosocial variables between the two groups using the χ2 test and t test. All data were further analyzed using a logistic regression model to adjust for confounding effects. Results Patients who had traits of developmental/personality disorders (adjusted odds ratio [OR]: 7.21, 95% confidence interval (CI): 1.21-42.9, P = .030), and those treated with psychoactive drugs (adjusted OR: 5.77, 95% CI 1.09-30.5, P = .039) required a longer treatment period (≥ 6 months). Conclusions Patients with personality/developmental traits and those with active psychiatric symptoms required a more extended treatment period in response to loss, suggesting the accumulation of negative factors in these patients; thus, more intensive and specialized care is necessary for these patients. Precise analysis of the coping style, attachment style, communication skills, and life history including relationship with the original family of the patients may have implications on the approach toward patients with complicated grief after perinatal loss. Studies with larger sample size are required to increase the reliability of the present findings, and future research should address the effects of the differential attachment and coping styles of patients with developmental/personality traits on the grief process.